Darwinian dynamics : evolutionary transitions in fitness and individuality - Michod, Richard E. (Princeton University Press, 1999)
In this book, Richard Michod offers a fresh, dynamical interpretation of evolution and fitness concepts. He argues that evolution has no enduring products; what matters is the process of genetic change. Whereas many biologists have focused on competition and aggression as determining factors in survival, Michod, by concentrating on the emergence of individuality at new and more complex levels, finds that cooperation plays an even greater role.